Adsorption and switching properties of nitrospiropyran on Bi(1 1 4) - Stremlau, Stephan; Maaß, Friedrich; Tegeder, Petra (Journal of physics. Condensed matter, 2017)
Spiropyrans are prototype molecular switches, which undergo a reversible photoinduced ring-opening/-closure reaction between the closed three-dimensional spiropyran (SP) and the open, planar merocyanine (MC) form. In solution the SP isomer is the thermodynamically stable form. Using high resolution electron energy loss spectroscopy, we resolve a thermally-activated irreversible ring-opening reaction of nitrospiropyran resulting in the MC form for coverages above one monolayer. Thus, the situation found in solution is reversed for the adsorbed molecules, since the MC form is more stable due to the modified energetics by the presence of the substrate. In addition, illumination with blue light (445 nm) induced also the ring-opening, while the photostimulated back-reaction could not be observed. The photoisomerization is driven by a substrate-mediated process, i.e. a charge transfer from the substrate into molecular states. The situation changes completely in the monolayer regime. Neither a thermally-assisted nor a photoinduced ring-opening reaction has been identified. We ascribe the suppression to sterical effects stabilizing the SP form due to the surface structure of Bi(1 1 4), which consists of straight atomic rows separated by rough valleys.